Feasibility of audio-motor training with the multisensory device ABBI: Implementation in a child with hemiplegia and hemianopia. (9th September 2022) - Tinelli, Francesca; Gori, Monica; Beani, Elena; Sgandurra, Giuseppina; Martolini, Chiara; Maselli, Martina; Petri, Stefania; Purpura, Giulia
Abstract: Spatial representation is crucial when it comes to everyday interaction with the environment. Different factors influence spatial perception, such as body movements and vision. Accordingly, training strategies that exploit the plasticity of the human brain should be adopted early. In the current study we developed and tested a new training protocol based on the reinforcement of audio-motor associations. It supports spatial development in one hemiplegic child with an important visual field defect (hemianopia) in the same side of the hemiplegic limb. We focused on investigating whether a better representation of the space using the sound can also improve the involvement of the hemiplegic upper limb in daily life activity. The experimental training consists of intensive but entertaining rehabilitation for two weeks, during which a child performed ad-hoc developed audio-motor-spatial exercises with the Audio Bracelet for Blind Interaction (ABBI) for 2 h/day. We administered a battery of tests before and after the training that indicated that the child significantly improved in both the spatial aspects and the involvement of the hemiplegic limb in bimanual tasks. During the assessment, ActiGraph GT3X+ was used to measure asymmetry in the use of the two upper limbs with a standardized clinical tool, the Assisting Hand Assessment (AHA), pre and post-training. Additionally, the study measured and recorded spontaneous daily life activity for at least 2 h/day. These results confirm that one can enhance perceptual development in motor and visual disorders using naturally associated auditory feedback to body movements. Highlights: Presentation of a new training protocol to support spatial development. Training based on the reinforcement of audio-motor associations. Application of the training in a child with hemiplegia and hemianopia.